Human Resource Flexibility and Its Impact on Organizational Ambidexterity: A Field Study on Jordanian Pharmaceutical Manufacturing Companies - Alkshali, Shaker; Alshaer, Sawsan (Jordan Journal of Business Administration, 2020)
This study aimed to investigate the impact of human resource flexibility on organizational ambidexterity in the Jordanian pharmaceutical manufacturing companies. The study was based on three dimensions to measure human resource flexibility, which are: skill flexibility, behavioral flexibility and practice flexibility. Organizational ambidexterity was measured using two dimensions, which are: exploratory and exploitative. The study was conducted on a random sample of (196) managers of all managerial levels in these companies. The researchers used the analytical descriptive approach to achieve the goals of this study. Numerous statistical methods were used to analyze the data, the most important of which is multiple regression coefficient.The study found that there are high levels of human resource flexibility and organizational ambidexterity in the Jordanian pharmaceutical manufacturing companies. Also, the results of the study reflected that there is a significant effect of the flexibility of human resources on organizational ambidexterity. In light of the results, the researchers presented several recommendations that could help the administrations of Jordanian pharmaceutical manufacturing companies raise the levels of organizational ambidexterity dimensions and find the equilibrium between them.